Exercise Activates p53 and Negatively Regulates IGF-1 Pathway in Epidermis within a Skin Cancer Model - Yu, Miao; King, Brenee; Ewert, Emily; Su, Xiaoyu; Mardiyati, Nur; Zhao, Zhihui; Wang, Weiqun (My University, 2016)
Exercise has been previously reported to lower cancer risk through reducing circulating IGF-1 and IGF-1-dependent signaling in a mouse skin cancer model. This study aims to investigate the underlying mechanisms by which exercise may down-regulate the IGF-1 pathway via p53 and p53-related regulators in the skin epidermis. Female SENCAR mice were pair-fed an AIN-93 diet with or without 10-week treadmill exercise at 20 m/min, 60 min/day and 5 days/week. Animals were topically treated with TPA 2 hours before sacrifice and the target proteins in the epidermis were analyzed by both immunohistochemistry and Western blot. Under TPA or vehicle treatment, MDM2 expression was significantly reduced in exercised mice when compared with sedentary control. Meanwhile, p53 was significantly elevated. In addition, p53-transcriptioned proteins, i.e., p21, IGFBP-3, and PTEN, increased in response to exercise. There was a synergy effect between exercise and TPA on the decreased MDM2 and increased p53, but not p53-transcripted proteins. Taken together, exercise appeared to activate p53, resulting in enhanced expression of p21, IGFBP-3, and PTEN that might induce a negative regulation of IGF-1 pathway and thus contribute to the observed cancer prevention by exercise in this skin cancer model.
Citation: Yu M, King B, Ewert E, Su X, Mardiyati N, Zhao Z, et al. (2016) Exercise Activates p53 and Negatively Regulates IGF-1 Pathway in Epidermis within a Skin Cancer Model. PLoS ONE 11(8): e0160939. doi:10.1371/journal.pone.0160939